Effect of filler loading of Clay filled low molecular weight Poly (Vinyl Chloride)/Acrylonitrile Butadiene rubber blends : dynamic mechanical analysis and swelling behaviour - Supri, A. Ghani; S. H. M. Salleh (Universiti Malaysia Perlis, 2010)
The effect of filler loading of clay on thermal properties and swelling index of LMWPVC/NBR rubber blends were investigated. Clay was used to increase many properties of the polymer matrix including the mechanical, thermal and barrier properties. Clay loading from 0 to 8 phr were prepared as filler for this purpose. Blend ratio of plastic to rubber was fixed as 70:30 (phr) with five different filler loading of clay. Blend of LMWPVC/NBR were produced by in-situ mixing technique using a Haake Rheomix Polydrive R 600/610 at 150oC with a rotor speed of 50 rpm. The result indicated that increasing the filler loading of clay has improved swelling resistance. The surfaces become rougher when the filler loading of the clay is increases. Besides that, the dynamic mechanical analyzer had been used to determine the glass transition temperature (Tg).